Appraising research in second language learning : a practical approach to critical analysis of quantitative research - Porte, Graeme Keith (Amsterdam ; Philadelphia : John Benjamins Pub. Co., 2010)
Designed for students of applied linguistics and second language acquisition on research training courses, practising language teachers, and those in training, this combination textbook/workbook is a set or recommended textbook on more than a hundred undergraduate and postgraduate courses worldwide. Now in its second edition, it remains the only book to provide specific advice and support to those wishing to learn a methodical approach to the critical analysis of a research paper. It seeks to answer a current need in the literature for a set of procedures that can be applied to the independent.
Appraising Research in Second Language Learning; Editorial page; Title page; LCC data; Table of contents; Preface; Notes on the second edition; Textbook and worked sample appraisals; Chapter 1. Introduction; Chapter 2. Introduction; Chapter 3. Introduction; Chapter 4. Introduction; Chapter 5. Method; Chapter 6. Method; Chapter 7. Method; Chapter 8. Results; Chapter 9. Discussion and conclusions; Workbook; Glossary of key terms in quantitative research; Appendices; Further reading; Index of main subject entries in textbook; The series Language Learning & Language Teaching.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Second language acquisition research -- Methodology; Second language acquisition research (Title); LANGUAGE ARTS & DISCIPLINES -- Alphabet; FOREIGN LANGUAGE STUDY; LANGUAGE ARTS & DISCIPLINES -- Linguistics; LANGUAGE ARTS & DISCIPLINES -- Grammar; LANGUAGE ARTS & DISCIPLINES; LANGUAGE ARTS & DISCIPLINES -- Spelling; Methodology; Methodologie; Sprachtest; Fremdsprachenlernen; Empirische Forschung; Tweedetaalverwerving; Onderzoek; Evaluatie; Onderzoeksmethoden; Kwantitatieve linguïstiek.; Fremdsprachenlernen; Sprachstatistik; Andraspråksinlärning -- forskning; Electronic book